REFLEKSI KEKERASAN DALAM NOVEL PENYAIR MERAH PUTIH KARYA MARDHIYAN NOVITA MZ - Yuliandri, Miki; Abdurahman, Abdurahman; Nasution, Bakhtaruddin (Universitas Negeri Padang, 2013)
The purpose of this study was to identify and describe the reflection of violence contained in the Penyair Merah Putih works Mardhiyan Novita MZ. The findings of this study include three related to the reflection of violence, namely: (1) the forms of violence against prominent reflection in the form of: (a) physical violence, beating, kicking and slapping, (b) psychological abuse, harass, threaten, and humiliate contained in the Penyair Merah Putih works Mardhiyan Novita MZ, (2) the causes of violence reflect misunderstanding main character and additional characters, (3) due to the onset of violence against the victim's reflection in the form of physical injuries and mental disabilities are perceived by the figures contained in the novel Penyair Merah Putih works Mardhiyan Novita MZ.